2005
DOI: 10.1073/pnas.0500008102
|View full text |Cite
|
Sign up to set email alerts
|

Ecosystem recovery after climatic extremes enhanced by genotypic diversity

Abstract: Contemporary climate change is characterized both by increasing mean temperature and increasing climate variability such as heat waves, storms, and floods. How populations and communities cope with such climatic extremes is a question central to contemporary ecology and biodiversity conservation. Previous work has shown that species diversity can affect ecosystem functioning and resilience. Here, we show that genotypic diversity can replace the role of species diversity in a species-poor coastal ecosystem, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

34
991
11
21

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,005 publications
(1,057 citation statements)
references
References 55 publications
34
991
11
21
Order By: Relevance
“…For example, decreased genetic variation in populations of barnacle larvae had a negative impact on larval recruitment (Gamfeldt et al 2005). In seagrass meadows, it has been shown that stands with less genetic variation are less productive, have lower diversity of associated flora and fauna, and are more susceptible toward extreme climate conditions (Reusch et al 2005). Direct effects on ecosystem services (fisheries harvest) were strongly related to the existence of genetically distinct populations of Sockeye salmon in the Pacific (Schindler et al 2010), and it seems possible that Baltic Sea salmon fishery and possibly other fisheries like the cod fishery may be benefitting in a similar way owing to genetically distinct local stocks (Nilsson et al 2001;Sterner 2007).…”
Section: Effects Of Genetic Variation On Ecosystem Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, decreased genetic variation in populations of barnacle larvae had a negative impact on larval recruitment (Gamfeldt et al 2005). In seagrass meadows, it has been shown that stands with less genetic variation are less productive, have lower diversity of associated flora and fauna, and are more susceptible toward extreme climate conditions (Reusch et al 2005). Direct effects on ecosystem services (fisheries harvest) were strongly related to the existence of genetically distinct populations of Sockeye salmon in the Pacific (Schindler et al 2010), and it seems possible that Baltic Sea salmon fishery and possibly other fisheries like the cod fishery may be benefitting in a similar way owing to genetically distinct local stocks (Nilsson et al 2001;Sterner 2007).…”
Section: Effects Of Genetic Variation On Ecosystem Functionmentioning
confidence: 99%
“…Clonality in macrophyte species such as Fucus vesiculosus, F. radicans, and Z. marina gives these species an immediate advantage to survive conditions benign for sexual reproduction, but at the same time lower their resistant to environmental stress (Reusch et al 2005) and give them a lower potential for evolutionary change compared to fully sexual species. It seems likely that decreased salinity will further reduce their level of sexual reproduction, and in the long run this may be problematic.…”
Section: What Is the Future Of The Baltic Sea Ecosystem?mentioning
confidence: 99%
“…Progress is being made in this area, but a serious issue is 50 that monitoring and modelling the delivery of ecosystem functions has been largely based 51 on the current set of environmental conditions (e.g. current climate, land use, habitat 52 quality).…”
mentioning
confidence: 99%
“…This reduces the population impacts of environmental perturbations [48] 201 and promotes resistance of ecosystem functions [49]. In addition, the persistence of 202 tolerant genotypes locally means that population recovery rates are likely to be higher, 203 leading to enhanced function recovery rates [48,50]. Adaptive genotypes can be present in 204 standing genetic variation, which is more likely at higher effective population sizes.…”
mentioning
confidence: 99%
“…Although much of the differentiation in traits observed in eelgrass across tidal heights is due to phenotypic plasticity (Dennison & Alberte, 1986; Li, Kim, Kim, Kim & Lee, 2013), there can be genetic differentiation in eelgrass growing at different depths (Kim et al., 2017; Ort et al., 2012), suggesting that there may be genetically based trait variation across depths. Trait differences can influence the intensity of competition between genotypes and patterns of coexistence, biomass accumulation, and population stability, with substantial consequences at the community and ecosystem level (Abbott & Stachowicz, 2016; Abbott et al., 2017; Ehlers, Worm & Reusch, 2008; Hughes & Stachowicz, 2004, 2011; Reusch, Ehlers, Hämmerli & Worm, 2005). …”
Section: Introductionmentioning
confidence: 99%